PENGARUH DOSIS PUPUK KANDANG SAPI TERHADAP PERTUMBUHAN DAN HASIL SERTA SIFAT FISIK DAN KIMIA TANAH PADA TANAMAN KACANG TANAH (Arachis hypogaea L.) - Julianus Jeksen (Agriculture Faculty of Flores University, 2014)
This study aims to examine the impact of cow manure dosage on the growth and yields of peanut plan and also on the physical and chemical characteristic of soil, as well as the optimum dosage of Bokasih fertilizer. This study uses block random design including 5 treatments and 4 repetitions. The treatment in this study is PK1 0 ton ha-1, PK2 10 ton ha-1, PK3 20 ton ha-1, PK4 30 ton ha-1, and PK5 40 ton ha-1. Meanwhile, the results of laboratory data analysis for the physical and chemical characteristic of soil are presented in tables and diagrams and are further described. The study indicates that the distribution of cow manure provides real impact on plant height, a number of leaves, leaf size at the age of 45 days after planting, that is to say, 45.29, 47.78, 48.11, 50.06, 50.81, and the age of 60 days after planting, that is to say, 65.30, 66.38, 67.60, 68.93, 70.46. There was also unreal impact on plant height, number of leaves, leaf size at the age of 15 and 30 days after planting, number of pod tan-1, number of containing pod tan-1, the weight of pod tan-1, and weight of fresh berangkasan tan-1. The distribution of cow manure has the impact of physical and chemical characteristic improvement on peanut plants. The optimum dose of cow manure that can enhance growth and yield of peanut plants has not been revealed in this research, whereas the optimum dose of the physical and chemical characteristics of soil is 40 ton ha-1.